Dupilumab for Atopic Dermatitis: The Silver Bullet We Have Been Searching for? - Tameez Ud Din, Ahsan (Cureus, 2020)
Atopic dermatitis is a chronic inflammatory condition of the skin affecting a large number of people worldwide. Historically, this condition has been managed by topical corticosteroids and general skincare measures. The inadequacy of these management strategies has always driven efforts to find better drugs. Dupilumab has been recently approved for the management of atopic dermatitis. It is a human monoclonal antibody that inhibits the binding of key interleukins involved in the pathogenesis of atopic dermatitis, thus blocking the signaling mechanisms and disrupting the disease progression. Dupilumab reduces the severity and associated symptoms of atopic dermatitis. It improves the life quality of patients and reduces the anxiety associated with the disease. Combination therapy of dupilumab and topical corticosteroids is more effective than dupilumab monotherapy. The treatment-related adverse events include headache, injection site reaction, conjunctivitis, nasopharyngitis, and herpes viral infections. Moreover, the simultaneous use of live vaccines with dupilumab is contraindicated. It is also beneficial in the management of asthma, chronic rhinosinusitis, and eosinophilic esophagitis. In this review, we have discussed the clinical efficacy and safety profile of dupilumab in the management of atopic dermatitis.